PERAN MASYARAKAT DALAM PELESTARIAN NILAI-NILAI WARISAN BUDAYA CANDI SAWENTAR KABUPATEN BLITAR - Aji, Nindi Jawining; Wirasanti, Niken (Jambura History and Culture Journal, 2024)
Understanding the values of Cultural Heritage as relics from the past can be considered as an attempt to understand the history that took place in it. Not only does it understand the past but, it also functions to understand the present and the future. The community plays an important role in maintaining the values contained in a Cultural Heritage. Sawentar Temple is one of the historical sites that has high cultural and historical value. The preservation of the historical values of Sawentar Temple requires active participation from the local community. This study aims to analyze the participation of the local community in maintaining and preserving the historical values of Sawentar Temple. The research method used in this paper is a qualitative approach by conducting interviews and direct observations of the community and parties directly related to Sawentar Temple. The results of this study show that community participation is very important in the process of preserving the values owned by Sawentar Temple through participation in the form of maintenance, education, promotion, and surveillance.